Collaborative Governance Dalam Pengembangan Newa Fun And Education di Desa Tambaknegara, Kecamatan Rawalo, Kabupaten Banyumas - Rizal Wahyu; Chamid Sutikno; Ariesta Amanda (Journal of Innovative and Creativity, 2025)
This study aims to examine the collaborative governance process in the development of Newa Fun and Education in Tambaknegara Village, Rawalo District, Banyumas Regency. The development of Newa Fun and Education involves numerous stakeholders, not only from the government but also non-governmental actors, including the community and the private sector. This is a characteristic of collaborative governance, necessitating a study to examine the collaborative process among these stakeholders. The research method used was qualitative with a descriptive approach and purposive sampling as the informant selection technique. This study employed the collaborative governance model developed by Russell Matthew Linden (2002). The study concluded that the collaborative governance process demonstrated a good level of cohesion, particularly based on four aspects: foundational collaboration, commitment, support, and collaborative leadership. However, there were still shortcomings in the relationship aspect, particularly in the lack of stakeholder trust in the development of Newa Fun and Education.